Four new species of Plakinidae (Porifera: Homoscleromorpha) from Brazil - Domingos, Celso; Moraes, Fernando; Muricy, Guilherme (Zootaxa, 2013)
Seven species of Plakinidae are currently known from Brazil, belonging to genera Plakina (P. trilopha), Plakinastrella (P. microspiculifera, P. onkodes), and Plakortis (P. angulospiculatus, P. halichondrioides, P. insularis, and P. microrhabdifera). In this study we describe four new species of the genera Plakinastrella and Plakortis, increasing the number of plakinid species in Brazil to eleven. Plakortis petrupaulensis sp. nov. is encrusting, light brown; the skeleton is disorganized with few traces of reticulation; lacunae are absent; the spicules are diods and tuberculate microrhabds; spheres are common and triods are absent. Plakortis spinalis sp. nov. is encrusting, gray, cartilaginous, has a reticulated ectosomal skeleton, and is distinguished by the spines in some of the diods and triods; microrhabds are also tuberculate and smooth spheres are common. Plakortis potiguarensis sp. nov. is encrusting, brown with gray tinges, and cartilaginous; the skeleton is disorganized and scarce, composed of thin, irregular diods, triods and relatively large microrhabds. Plakinastrella globularis sp. nov. has a globular shape and dark blue color in vivo; the ectosomal skeleton has a double tangential reticulation and the choanosomal skeleton is reticulated. The spicules are diods, triods, calthrops and microrhabds; spheres are common. Two of the new species have characters previously unknown in their respective genera: the spined diods and triods of Plakortis spinalis sp. nov. and the blue color and microrhabds of Plakinastrella globularis sp. nov. The presence of microrhabds in Plakinastrella suggests a close relationship of this genus with Plakortis.